PHILOLOGY (TAHQIQ AL_MAKTUTAT) IN NUSANTARA AND ARAB WORLD:A HISTORICAL STUDY (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
This study aims to review the history of the development of philology in Nusantara the Arab world. Philological activity in Arabia is not something new, but it has been going on before Islam came, then Islam strengthens these scientific activities. This research is library research that uses a qualitative descriptive method. The results of this study indicate that in the classical period, there was an intersection between Eastern and Western cultures, resulting in a study of ancient texts from both cultures which impacted the progress of science and civilization. Although Arabic philology experienced a setback in the Middle Ages, in the modern era, scientists have begun to awaken awareness to revive the spirit to explore ancient texts in various areas in the Arab and Islamic regions. Nusantara as part of the Islamic world also has a wealth of manuscripts that need to be explored. Historically, philology that developed in the Arab and Islamic worlds did not only refer to the study of ancient texts and then presented them in a new face, but also included the translation and study of the culture of a nation through the legacy of old texts.